A tumor microenvironment-related risk model for predicting the prognosis and tumor immunity of breast cancer patients - Geng, Shengkai; Fu, Yipeng; Fu, Shaomei; Wu, Kejin (Frontiers in Immunology, 2022)
Background: This study aimed to construct a tumor microenvironment (TME) related risk model to predict the overall survival (OS) of patients with breast cancer. Methods: Gene expression data from the Cancer Genome Atlas (TCGA) was used as a training set. Differentially expressed gene (DEG) analysis, Prognosis analysis, Weighted gene co-expression network analysis (WGCNA), Least Absolute Shrinkage and Selection Operator (LASSO) regression analysis and Wald stepwise Cox regression were performed to screen for the TME-related risk model. 3 Gene Expression Omnibus (GEO) databases were used to validate the predictive efficiency of the prognostic model. TME-risk related biological function was investigated using the gene set enrichment analysis (GSEA) method. Tumor immune and mutation signatures were analyzed between low and high TME-risk groups. The patients’ response to chemotherapy and immunotherapy were evaluated by the tumor immune dysfunction and exclusion (TIDE) score and immunophenoscore (IPS). Results: 5 TME-related genes were screened for constructing a prognostic signature. Higher TME-risk scores were significantly associated with worse clinical outcomes in the training and validation set. Correlation and stratification analyses also confirmed the predictive efficiency of the TME-risk model in different subtypes and stages of breast cancer. Furthermore, immune checkpoint expression and immune cell infiltration were found to be upregulated in the low TME-risk group. Biological processes related to immune response functions were proved to be enriched in the low TME-risk group through GSEA analysis. Tumor mutation analysis, TIDE and IPS analyses showed that high TME-risk group had more tumor mutation burden (TMB) and responded better to immunotherapy. Conclusion: The novel and robust TME-related risk model had strong implication for breast cancer patients in OS, immune response, and therapeutic efficiency.